Coach there is hope - avoiding stress and burnout - Rosemond, L. (2015 World Rowing Coaches Conference, 19-22 Nov 2015, Florida, USA, 2015)
The content of the presentation includes: - What is stress? What is burnout? - Family first, - We all have a story, - Long work hours, - Poor sleeping habits/poor physical health, - Lack of physical health maintenance, - Hiring and supervising, - Caring: constantly, - Emotional health, - Avoiding the arrogance syndrome, - Is more really better? - Accountability partner, - Managing conflict.